Aggregate Subgrade Improvements Using Quarry By-Product Fines: A Case Study. Issue 8 (August 2022) - Qamhia, Issam I. A.; Wang, Han; Tutumluer, Erol; Short, Michael
This paper presents a case study for constructing aggregate subgrade improvement (ASI) layers using quarry by-product aggregates (QBA)—a quarry mix of large primary crushed rocks (PCR) and sand-sized quarry fines. The construction took place at Larry Power Road in Bourbonnais Township in Kankakee County, Illinois, where the Illinois Department of Transportation (IDOT) placed two QBA mixes for performance evaluation. The first mix (QBA_M1) consisted of 45% quarry by-products (QB) and 55% railroad ballast-sized PCR. The second mix (QBA_M2) consisted of 31% QB and 69% PCR. Two conventional ASI sections with only PCR were also constructed. All sections consisted of a 229 mm (9 in.) QBA/PCR layer topped with a 76 mm (3 in.) thick dense-graded capping layer. Laboratory studies preceded the construction to recommend optimum QB percentages for the QBA materials and construction practice. The quality and uniformity of the construction was ensured through field testing using dynamic cone penetrometer (DCP), lightweight deflectometer (LWD), and falling weight deflectometer (FWD). The segregation potential of the QBA mixes was monitored by visual inspection, aggregate stockpile sampling, and image analysis techniques. Short-term field evaluation of the constructed QBA layers, particularly QBA_M2 with 31% QB, showed no evidence of major segregation. The QBA ASI layers had slightly lower but comparable strength and stiffness profiles to the conventional ASI sections. The use of QBA materials in ASI was therefore field validated in this case study as a sustainable construction practice to provide stable pavement foundation layers.